The Transition to a State Medical Service
1942-08 1942 1940s 8 pages paid to the municipality by the Ministry of Health on the understanding that he shall be permitted to give part time services to the Ministry. The same general arrangements will apply in the case of junior officers employed by municipalities, but in certain cases it is likely that officers of existing health departments will wish to become officers of the Ministry of Health, and that the municipality may be obliged to find others to manage its environmental services. (37) The chief of the local officers of the Ministry of Health will be the Area Health Officer, corresponding in status to the Medical Officer of Health for environmental service. Although the work of the Area Health Officer will be almost entirely administrative, he will control clinical services, and will be required to have had adequate clinical experience. He will, therefore, as a rule, be selected from the members of the National Health Service, all of whom, whatever their speciality, will have had to put in a certain number of years as general medical practitioners. (38) In order that municipalities may not be deprived of some field from which they may recruit medical officers of suitable skill, it must remain possible for doctors who form part of the National Service to apply for such posts and to contract out of the National Service for so long as they may continue to enjoy them. It is anticipated that within one or two generations the Ministry of Health will find itself in a position to take over the environmental services when such contracting out arrangements will no longer be necessary. (39) It is likely that laboratory services will need to be shared between national and hospital authorities. (40) Maternity services and control of district nursing associations should be taken over with the hospitals, but Home Help Services, day nurseries, etc., will remain municipal responsibilities. (41) Clinic buildings and services will also be taken over and, in most cases, the doctors serving them will enter the National Service. (42) The Health Visitor has lately assumed a place of increasing importance in health administration. Her function should be the prevention of ill health, for which she is trained, and not the treatment of minor diseases, which she is so prone to undertake. The Union considers that health visitors should remain under the control of the environmental health services, although they might perform some duties for the Area Health Committees. (G) CONVALESCENT HOMES, CAMPS, Etc. (43) It is reasonably certain that a very considerable extension of these services will be a prominent feature of the future Medical Services. They will help to provide the city child with those advantages which have been experienced by evacuees during the war period. They will supply the last stage in industrial rehabilitation and will be amongst the most potent factors in preventing the development of threatened ill-health. They will require a new type of management and will cope with cases whose cure is not yet complete but can best be brought to a successful outcome by final treatment given in country surroundings. (44) The Ministry should take over all suitable Convalescent Homes, Camps, etc., and administer them as part of the National Health Service. (45) It is suggested that these convalescent homes and holiday camps may well excite the interest and contributions of those who have hitherto supported voluntary hospitals, and that this might prove an important factor in popularising their more extended use. (H) DENTAL SERVICES (46) All those who are practising dentistry, including mechanics, would have a right to join the State Service. (47) Their status and emoluments would depend upon the class of work which they are able to undertake, but dental surgeons would neither be paid less than medical practitioners of similar experience, nor be deemed to occupy an inferior position with regard to status or administrative responsibility. (I) MEDICAL EDUCATION (48) In assuming the responsibilities of the Privy Council under the Medical Acts, the Ministry of Health would find itself responsible for medical education, as it would also be responsible for the education of both dental and nursing personnel, as well as for that necessary in various auxiliary services. (49) University faculties and the Royal Colleges would be subsidised to carry out educational work on behalf of the Ministry, and this would probably be extended to include more regular postgraduate work than has hitherto been possible. Facilities for instruction would be provided in the State hospitals. (50) A State examination and degree would be the single portal of entrance to the profession for all, and no higher degree than this would be essential for any medical appointment controlled by the State. The Union believes that the medical course should be very considerably shortened in view of the fact that all entrants into the State service would be required to practise under supervision for at least two years, as House Physicians, House Surgeons, or in special departments. They would thus serve an apprenticeship of much more value than routine school instruction. (51) Higher education would continue to be available and perhaps compulsory for both physicians and surgeons, and this would be accompanied, in the case of successful students, by increased status and emoluments. (52) Medical education would need to include a special course for those whose life's work is to be the teaching of students. This has hitherto been much neglected, because teaching has been confined to the staffs of hospitals, who have in turn been selected because of their particular skill in entirely different spheres, or because of their possession of degrees which are in no way any guarantee that they are able to act as efficient teachers. 5 292/847/1/4